The Influence Of Model Problem-Based Learning, Model Project-Based Learning, And Model-Based Multicultural Learning On Prosocial Behavior Primary School Students In Surabaya - Danang Prastyo; Budi Eko Soetjipto; Syamsul Hadi; Ari Sapto (STMIK Dharma Wacana, 2023)
This research aims to determine the influence of the problem-based learning model, project-based model, and multicultural-based learning model on the prosocial behavior of elementary school students in Surabaya. The research applied is experimental research. The design in this research uses a nonequavalent Control Group Post-test Design. The research population is SDN Surabaya with research samples of fifth-grade elementary school students at SDN Margerejo I, SDN Sumur Welut III Surabaya, SDN Dukuh Menanggal 601 Surabaya. The data collection technique uses a questionnaire with 30 questions, while the research instrument uses the Measure of Prosocial Tendencies by adapting Carlo's. The data analysis technique uses the T-test. From the results of data processing, it can be concluded that there is an influence of the Model Problem Based Learning, Model Project Based Learning, and Model Multicultural Based Learning on the prosocial behavior of elementary school students in Surabaya